SLANG LANGUAGES USED IN A MOVIE ENTITLED BABY DRIVER (A Sociolinguistics Approach) - Risa Aulia; Djatmika Djatmika (Elite : English and Literature Journal, 2018)
This article discusses about slang languages used by the characters in Baby Driver movie. Data in the form of conversations which contain slang languages were collected from Baby Driver movie script. The collected data then were analyzed by applying Sociolinguistics approach to see the types, forms, and the functions of slang used in Baby Driver. The findings show that there are three types of slang used in Baby Driver movie including society, criminal, and police slang. Second, there are two forms of slang used by the characters, words, and phrases. Meanwhile, there are ten functions of slang. They are to address, to form intimate atmosphere, to express impression, to show intimacy, to reveal anger, annoyance, or disappointment, to threaten or to mock, to express a blaming or accusing, to show high spirit, to persuade someone in conversation, and to be secret or as an identification marker.